Firms Price Markups and Returns to Scale in Imperfect Markets - Bulgaria and Hungary - Rumen Dobrinsky; Gabor Korosi; Nikolay Markov; Laszlo Halpern (Hungarian Academy of Sciences, Institute of Economics, 2004)
Under perfect competition and constant returns to scale, firms producing homogeneous products set their prices at their marginal costs which also equal their average costs. However, the departure from these standard assumptions has important implications with respects to the derived theoretical results and the validity of the related empirical analysis. In particular, monopolistic firms will charge a markup over their marginal costs. We show that firms' markups tend to be directly associated with the employed production technology, more specifically with their returns to scale. Accordingly, we analyze the implications for the markup ratios from the incidence of non-constant returns to scale. We present quantitative results illustrating the effect of the returns to scale index on the firms' price markups, as well as the relationship between the two indicators, on the basis of firm-level data for Bulgarian and Hungarian manufacturing firms.
Keywords: C23; D21; D24; 330; markup pricing; market imperfections; return to scale; Bulgaria; Hungary